The Association of Meaningfulness, Well‐Being, and Engagement with Absenteeism: A Moderated Mediation Model. Issue 3 (22nd May 2013) - Soane, Emma; Shantz, Amanda; Alfes, Kerstin; Truss, Catherine; Rees, Chris; Gatenby, Mark
Abstract We theorized that absence from work is a resource‐based process that is related to perceived meaningfulness of work, well‐being, and engagement. Broaden‐and‐build theory (Fredrickson, 1998, 2001) and engagement theory (Bakker, Schaufeli, Leiter, & Taris, 2008; Kahn, 1990) were used to develop a framework for explaining absence. Results of a study of 625 employees and human resource records of subsequent absenteeism data for a three‐month period supported our hypotheses that meaningful work increases engagement with work, and that engagement is associated with low levels of absenteeism. Furthermore, data showed that engagement fully mediated the relationship between meaningfulness and absence, and that well‐being strengthened the relationship between meaningfulness and engagement. The results have implications for understanding the role of individual‐level resources in the workplace, and how meaningfulness, well‐being, and engagement influence absence.